Single CpG hypermethylation, allele methylation errors, and decreased expression of multiple tumor suppressor genes in normal body cells of mutation‐negative early‐onset and high‐risk breast cancer patients. Issue 6 (25th April 2018) - Böck, Julia; Appenzeller, Silke; Haertle, Larissa; Schneider, Tamara; Gehrig, Andrea; Schröder, Jörg; Rost, Simone; Wolf, Beat; Bartram, Claus R.; Sutter, Christian; Haaf, Thomas
Abstract : To evaluate the role of constitutive epigenetic changes in normal body cells of BRCA1 / BRCA2 ‐mutation negative patients, we have developed a deep bisulfite sequencing assay targeting the promoter regions of 8 tumor suppressor (TS) genes ( BRCA1, BRCA2, RAD51C, ATM, PTEN, TP53, MLH1, RB1 ) and the estrogene receptor gene ( ESR1 ), which plays a role in tumor progression. We analyzed blood samples of two breast cancer (BC) cohorts with early onset (EO) and high risk (HR) for a heterozygous mutation, respectively, along with age‐matched controls. Methylation analysis of up to 50, 000 individual DNA molecules per gene and sample allowed quantification of epimutations (alleles with >50% methylated CpGs), which are associated with epigenetic silencing. Compared to ESR1, which is representative for an average promoter, TS genes were characterized by a very low (< 1%) average methylation level and a very low mean epimutation rate (EMR; < 0.0001% to 0.1%). With exception of BRCA1, which showed an increased EMR in BC (0.31% vs. 0.06%), there was no significant difference between patients and controls. One of 36 HR BC patients exhibited a dramatically increased EMR (14.7%) in BRCA1, consistent with a disease‐causing epimutation. Approximately one third (15 of 44) EO BC patients exhibited increased rates of single CpG methylation errors in multiple TS genes. Both EO and HR BC patients exhibited global underexpression of blood TS genes. We propose that epigenetic abnormalities in normal body cells are indicative of disturbed mechanisms for maintaining low methylation and appropriate expression levels and may be associated with an increased BC risk. Abstract : What's new? Cancer can change patterns of DNA methylation, with widespread loss of methylation but also localized increases in methylation. Here, the authors analyzed blood cells, looking for differences in methylation between breast cancer patients and healthy persons. They developed a deep bisulfite sequencing assay to specifically test the promoter regions of 8 tumor suppressor genes, plus the estrogen receptor gene, along with reduced tumor suppressor gene expression. They found that breast cancer patients showed increased methylation changes in multiple tumor suppressor genes, reduced tumor suppressor gene expression. Thus, epigenetic abnormalities could indicate disruptions in the mechanisms that maintain proper methylation, and could signal increased tumor risk.